GSH/pH-responsive copper-based cascade nanocomplexes inducing immunogenic cell death through cuproptosis/ferroptosis/necroptosis in oral squamous cell carcinoma - Yi Sun; Enze Li; Wenzhao Zhong; Zhaoming Deng; Ziyao Zhou; Ka Hong Wong; Xiangwei Li (Materials Today Bio)
Oral squamous cell carcinoma (OSCC) remains a formidable challenge due to high recurrence rates and limited efficacy of conventional treatments. Immunotherapy holds potential, but its effectiveness is often restricted by low patient responsiveness. This study presents a novel therapeutic strategy using GSH/pH-responsive copper-based cascade nanocomplexes to induce immunogenic cell death (ICD) in OSCC. The fabricated nanocomplex, PC@B-H, leverages the acidic and reducing tumor microenvironment to release copper ions and plumbagin, triggering a cascade of cell death mechanisms including cuproptosis, ferroptosis, and necroptosis. This multifunctional system not only enhances oxidative stress but also depletes glutathione, promotes lipid peroxidation, and disrupts mitochondrial function, leading to robust tumor inhibition. Additionally, the induction of ICD facilitates dendritic cell maturation and cytotoxic T lymphocyte infiltration, providing durable anti-tumor immunity. The study demonstrates that PC@B-H achieves a 92.3 % tumor growth inhibition rate with minimal systemic toxicity, offering a promising avenue for enhancing the efficacy of OSCC treatment through combined cell death pathways and immune activation.